Maintenance of real objects and their verbal designations in working memory - Kaiser, Stefan; Kopka, Marie-Luise; Rentrop, Mirjam; Walther, Stephan; Kronmüller, Klaus-Thomas; Olbrich, Robert; Weisbrod, Matthias; Stippich, Christoph (Neuroscience letters, 2010)
The present study investigated the neural correlates of working memory maintenance for real objects in contrast to their verbal designations. For this purpose we employed a delayed match-to-sample task using functional magnetic resonance imaging. The conjunction of load effects for objects and for words revealed a common bilateral network with main foci in the ventrolateral prefrontal cortex and the intraparietal sulcus. Load effect for objects in comparison to load effect for words revealed stronger activation of bilateral precuneus, which suggests the use of mental imagery of objects and object features. The opposite comparison load words versus load objects showed premotor and auditory areas to be activated in association with phonological rehearsal. The bilateral common activation indicates overlapping codes for real-world objects and their verbal designations. Importantly, there is also a dissociation between maintenance of words and objects, which indicates that phonological rehearsal and mental imagery are employed to different degrees.
Online veröffentlicht am 20. November 2009
Gesehen am 28.02.2023